Genetic diversity among pomegranate germplasm assessed by microsatellite markers - Badenes, María L.; Zuriaga, Elena; Bartual, Julián; Pintová, Jitka (2018)
Pomegranate (Punica granatum L.) belongs to the Punicaceae family and is native from the region between Iran to the Himalaya in Northern India. It has been cultivated and naturalized over the whole Mediterranean region since ancient times. Normally consumed as a fresh fruit, pomegranate can also be used to obtain transformed products such as juice, jam or preserves. Moreover, in recent years the pomegranate has shown great importance for human health because of the high antioxidant content of its juice and peel. Improvement of the crop and fruit quality are the main goals in breeding programs. Pomegranate species shows high diversity of pomological traits, which is very interesting for improvement of the crop by breeding. One of the main tools for breeding are the germplasm resources and their genetic diversity. In this study, 96 accessions belonging to the IVIA’s collection were analysed using 18 microsatellite markers developed from pomegranate. The plant material come from nine countries and included some hybrids and accessions from unknown origin. A total of 111 alleles were obtained. They were used for addressing the molecular genetic diversity and population structure of the collection. Knowledge of the substructure and diversity of the collection will allow us to manage the genetic resources as well as planning the incorporation of new materials in the future. The goal is to select the best plant material for the pomegranate breeding program.